Penilaian Intensifikasi PBB P2 dalam Meningkatkan Penerimaan Daerah - Mega Tunjung Hapsari; Tjahjanulin Domai; Firda Hidayati (Jurnal Akuntansi dan Pajak, 2018)
The aims of this research to analyze the assessment of intensification on rural and urban land and building tax (PBB P2) in Tulungagung Regency in order to increase PBB P2 revenue through Davey Analysis based on four criteria of local tax assessment, namely: sufficiency and elasticity, justice, administrative ability, and influence of incentive. This research is classified as descriptive research through qualitative approach. Data analysis used interactive models by Miles, Huberman, and Saldana (2014). The research result based on empirical data, theoretical study, and normative study showed that intensification in the forms of technical guidance and SISMIOP data base maintenance are give negative implication on administrative ability assessment due to lack of quality and quantity of human resources. While, monitoring and delivery of SPPT can give positive implication on judgment of justice. Then, presence of socialization on regional regulation and reward giving and sanction imposition, are give positive implication on assessment of elasticity and influence of incentive.